The Role of Perceived Organizational Support and Employee Engagement on Turnover Intention: Evidence from a Public Accounting Firm in Indonesia - Tarigan, Emme Riahta Br; Salendu, Alice (Dinasti International Journal of Management Science, 2026)
High turnover intention remains a strategic challenge for public accounting firms due to its detrimental impact on audit quality, operational continuity, and human capital sustainability (Hom et al., 2017). Grounded in Organizational Support Theory (Eisenberger et al., 1986), this study examines the effects of perceived organizational support (POS) and employee engagement on turnover intention and identifies the dominant predictor within a professional service context. Using a quantitative cross-sectional design, data were collected from 110 auditors at the Associate and Senior Associate levels in a public accounting firm in Indonesia. POS was measured using the Survey of Perceived Organizational Support (Eisenberger et al., 1986), employee engagement was assessed using the ISA Engagement Scale (Soane et al., 2012), and turnover intention was measured using the Turnover Intention Scale (Bothma & Roodt, 2013). Data were analyzed using descriptive statistics, Pearson correlation, and multiple regression analysis. The results reveal that both perceived organizational support and employee engagement have significant negative relationships with turnover intention, consistent with prior empirical findings (Riggle et al., 2009; Kurtessis et al., 2017). However, perceived organizational support demonstrates a stronger and more consistent predictive effect. These findings underscore the critical role of organizational support mechanisms in reducing employees’ intention to leave and provide empirical support for Organizational Support Theory within the context of professional service firms in emerging economies.